Multiple Functions of ATG8 Family Proteins in Plant Autophagy - Bu, Fan; Yang, Mingkang; Guo, Xu; Huang, Wei; Chen, Liang (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is a major degradation process of cytoplasmic components in eukaryotes, and executes both bulk and selective degradation of targeted cargos. A set of autophagy-related (ATG) proteins participate in various stages of the autophagic process. Among ATGs, ubiquitin-like protein ATG8 plays a central role in autophagy. The ATG8 protein is conjugated to the membrane lipid phosphatidylethanolamine in a ubiquitin-like conjugation reaction that is essential for autophagosome formation. In addition, ATG8 interacts with various adaptor/receptor proteins to recruit specific cargos for degradation by selective autophagy. The ATG8-interacting proteins usually contain the ATG8-interacting motif (AIM) or the ubiquitin-interacting motif (UIM) for ATG8 binding. Unlike a single ATG8 gene in yeast, multiple ATG8 orthologues have been identified in the plant kingdom. The large diversity within the ATG8 family may explain the various functions of selective autophagy in plants. Here, we discuss and summarize the current view of the structure and function of ATG8 proteins in plants.